2021
DOI: 10.1111/ans.16760
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a novel method for assessing elasticity of internal anal sphincter using ultrasonic real‐time tissue elastography

Abstract: Real‐time tissue elastography is a new method available on ultrasonography for the quantitation of strain. Evaluating anorectal function using real‐time tissue elastography has not been reported. We established a novel method of quantitating the degree of hardness of the internal anal sphincter, using real‐time tissue elastography on endoanal ultrasonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…RTE was performed on each patient with freehand manual compression in the anterior, left, posterior, and right positions to confirm that the IAS was well-detected and its elasticity could be assessed. Fukui et al RTE method was followed [13], and IAS elasticity-the stiffness of the IAS at 6 o'clock of the anus-was recorded and evaluated (hardest (0) to softest (255), decrease in elasticity means sclerotic change). Figure 2b presents posterior IAS image evaluation.…”
Section: Real-time Tissue Elastographymentioning
confidence: 99%
See 1 more Smart Citation
“…RTE was performed on each patient with freehand manual compression in the anterior, left, posterior, and right positions to confirm that the IAS was well-detected and its elasticity could be assessed. Fukui et al RTE method was followed [13], and IAS elasticity-the stiffness of the IAS at 6 o'clock of the anus-was recorded and evaluated (hardest (0) to softest (255), decrease in elasticity means sclerotic change). Figure 2b presents posterior IAS image evaluation.…”
Section: Real-time Tissue Elastographymentioning
confidence: 99%
“…Hence, we speculated that CRTinduced fibrosis may induce IAS sclerosis, which may consequently be associated with postoperative anal dysfunction. Therefore, in 2021, Fukui established a method to quantify IAS hardness and defined it as elasticity using real-time tissue elastography (RTE) on the endoanal ultrasonography (EAUS) [13]. Santoro et al have already reported that endorectal ultrasonography was useful in assessing the depth of submucosal invasion in early rectal cancer [14], but there are no reports of its use in functional assessment so far.…”
Section: Introductionmentioning
confidence: 99%